If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 + -4k = 5 Solving 13 + -4k = 5 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + -4k = 5 + -13 Combine like terms: 13 + -13 = 0 0 + -4k = 5 + -13 -4k = 5 + -13 Combine like terms: 5 + -13 = -8 -4k = -8 Divide each side by '-4'. k = 2 Simplifying k = 2
| 4u^2+25u+31=0 | | 16y^2+16y+4=0 | | 9a^2=81 | | 6y+5=4y-7 | | 3-2(a+2+a)=5a+8 | | y^2+y-12=0 | | 12x^2+9=-6x | | 1x-4(x+3)=4-2x | | 9-18x+9x^2=0 | | 2u^2+9u-18=0 | | 3x^2+10xy+5y^2+20=0 | | y-(y+3)=y+y | | 5w^2+11w-2=0 | | 6p^2=-11p-40 | | 5(b-4)=10b+4 | | 5(b-4)=10y+4 | | 4v^2+8v+15=0 | | 8x+10=570 | | 2k^2-20=-k | | 4y+5=31 | | 4x^3+5x+1=0 | | 45x^2-120xy+80y^2=0 | | 6x^2-10x+10=0 | | 9x^3+39x^2+42x=0 | | 6y-2=5y+8 | | 16y+12=9y+3 | | -7p-15=-2p+11 | | 4x^2=x+4 | | 10w+19=4b-5 | | -(7y+2)-(-6y-4)=-3 | | 10+19=4b-5 | | 10-8z=-11z+7 |